MODEL PENGEMBANGAN BUDAYA RELIGIUS DI SEKOLAH MENENGAH KEJURUAN AS-SYAFI’I JEMBER - Royani, Ahmad (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2023)
Being concerned with aspects of morality among adolescents, including among students, has caused many parties. Educational institutions are expected to be able to internalize religious values ​​in students' lives. Referring to the theory developed by Ralp W Tyler, the most important element in the development of religious culture in an organizational institution is the process of exercises carried out by the school institution itself, which will later build a culture with this exercise. This paper wants to describe the model for the development of religious culture in the As-Syafi'i Vocational High School, Jember. While the method used in this paper is qualitative with a data mining model through interviews, observation, and documentation. The conclusion in this paper is; the development of religious culture in students at As-Syafi'I Vocational School Jember is carried out by instilling systematic behavior or manners in the practice of their religion so that personality, character, attitude, and morality are formed that are noble, noble, and responsible, good relationship with Allah Swt, with fellow humans and with the surrounding natural environment. For this reason, the values ​​developed at As-Syafi'I Jember Vocational School, namely emphasizing morality, achievement, discipline, and environmental culture.